Bibliometric Analysis of the Impact of Early Marriage on Adolescents - Yuliastuti, Anie; Mubin, Mohammad Fatkhul; Ernawati, Ernawati; Pranata, Satriya (GLOBAL HEALTH SCIENCE GROUP, 2024)
Marriages that are carried out without being prepared mentally, physically or financially can cause problems for the continuation of the marriage. The impacts that arise also vary, starting from the health of mothers who are pregnant at a young age, the condition of children born to young mothers, the psychology of the couple, and what is even worse is the impact of divorce. In this research study, researchers need information about innovations and new trends for the topic. Objective: The purpose of this research is to explore the number of publication trends and citation trends with the highest number of publications, as well as which fields are approved for publication, network visualization, overlay visualization, and density visualization through bibliometric analysis. Method: This research uses bibliometric analysis. Records were identified through database searches https://app.dimensions.ai/, continued through the PRISMA flowchart. Publications from 2019 – 2023, focus on psychology, health science, health services and systems, clinical science. The type of publication is an article, the data is analyzed using VOSviewer, then a review is carried out by the co-occurrence and co-author. Results: A search for publications on the topic of the psychosocial impact of early marriage resulted in 200,648 articles. Next, screening was carried out using predetermined criteria and the results obtained were 13,330 articles. The highest publication was in 2021, while the lowest was in 2023. These trends and topics are early pregnancy, early sexual debut, marital conflict, the impact of early marriage, dissatisfaction with sexual relations, psychological distress. The majority of researchers are in Africa, Bangladesh, Ethiopia, Nepal, South Asia and Uganda. Conclusions: The topic of psychosocial problems in early marriage must be developed further in various countries, especially Africa and Bangladesh.